RNA‐Peptide nanoplexes drug DNA damage pathways in high‐grade serous ovarian tumors. Issue 1 (19th January 2018) - Dreaden, Erik C.; Kong, Yi Wen; Quadir, Mohiuddin A.; Correa, Santiago; Suárez‐López, Lucia; Barberio, Antonio E.; Hwang, Mun Kyung; Shi, Aria C.; Oberlton, Benjamin; Gallagher, Paige N.; Shopsowitz, Kevin E.; Elias, Kevin M.; et al.
Abstract: DNA damaging chemotherapy is a cornerstone of current front‐line treatments for advanced ovarian cancer (OC). Despite the fact that a majority of these patients initially respond to therapy, most will relapse with chemo‐resistant disease; therefore, adjuvant treatments that synergize with DNA‐damaging chemotherapy could improve treatment outcomes and survival in patients with this deadly disease. Here, we report the development of a nanoscale peptide‐nucleic acid complex that facilitates tumor‐specific RNA interference therapy to chemosensitize advanced ovarian tumors to frontline platinum/taxane therapy. We found that the nanoplex‐mediated silencing of the protein kinase, MK2, profoundly sensitized mouse models of high‐grade serous OC to cytotoxic chemotherapy by blocking p38/MK2‐dependent cell cycle checkpoint maintenance. Combined RNAi therapy improved overall survival by 37% compared with platinum/taxane chemotherapy alone and decreased metastatic spread to the lungs without observable toxic side effects. These findings suggest (a) that peptide nanoplexes can serve as safe and effective delivery vectors for siRNA and (b) that combined inhibition of MK2 could improve treatment outcomes in patients currently receiving frontline chemotherapy for advanced OC.